Pengaruh Penggunaan Busi Standar, Dan Busi Iridium Terhadap Daya Dan Torsi Pada MesinYamaha Force One - Prayogi, Yoga (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2023)
Abstract A spark plug is a part of an internal combustion engine with an electrode tip in the combustion chamber. Spark plugs are installed to burn gasoline that has been compressed by the piston. Spark plugs are electric spark plugs. types of spark plug types include standard, iridium and platinum spark plugs. Each type of spark plug affects engine performance. Performance testing is done to find out which spark plug is right for the type of 4 stroke engine. The test results show the difference in maximum power generated from standard spark plugs is 11.7 HP at 6500 rpm. The power generated from the iridium spark plug is 12.1 HP at 6250 rpm. the maximum torque difference generated from the standard spark plug is 13.68 Nm at 5750 rpm while the power generated from the Iridium Spark Plug is 13.93 Nm at 5500 rpm. Iridium spark plugs have better ignition than standard spark plugs because the combustion is focused at one point the use of iridium spark plugs is a spark plug with an electrode core tip (the part that sparks) alloy (mixed metal) spark plug construction iridium alloy combination produces better material resistant in extreme conditions melting point up to 2500 ° C. Keywords; Performance; Spark Plug; 4 Stroke. Abstrak Busi adalah suatu suku cadang pada mesin pembakaran dalam dengan ujung elektroda pada ruang bakar. Busi dipasang untuk membakar bensin yang telah dikompres oleh piston. Percikkan busi berupa percikkan elektrik. jenis jenis busi ini antara lain adalah busi standart, iridium dan platinum. Masing-masing jenis busi mempengaruhi performa mesin. Pengujian performa dilakukan guna mencari tau busi mana yang tepat untuk jenis mesin 4 tak. Hasil pengujian menunjukan perbedaan daya maksimal yang dihasilkan dari busi standar adalah 11,7 HP pada rpm 6500. Daya yang dihasilkan dari busi iridium 12.1 HP pada rpm 6250. perbedaan torsi maksimal yang dihasilkan dari Busi standar adalah 13.68 Nm pada rpm 5750 sementara itu daya yang dihasilkan dari Busi Iridium 13.93 Nm pada rpm 5500. Busi Iridium memiliki pengapian yang lebih baik dari Busi standar karena pembakarannya fokus pada satu titik penggunaan busi iridium adalah busi dengan ujung inti elektroda (bagian yang memercikan api) alloy (metal campuran) konstruksi busi kombinasi iridium alloy menghasilkan lebih baik materialnya tahan dalam kondisi ektrem titik meleleh sampai 2.500 °C Kata kunci: Kata kunci: Performa; Busi; 4 Tak